DICENDI VERBS AND MODALIZATION IN THE CONTEXT OF HEALTH SURVEILLANCE: A DISCOURSIVE ANALYSIS (Editora Impacto Científico, 2025)
This chapter analyzes the recontextualization of scientific discourse concerning the relationship between the Zika virus and microcephaly on the G1 news portal, focusing on the dicendi verbs used to introduce authority voices. From the perspective of Discourse Analysis and science communication studies, it investigates the linguistic-discursive mechanisms that indicate degrees of certainty, conviction, and hesitation. The analysis considers the multiplicity of voices, textual polyphony, and the knowledge-power relationship, as proposed by Bakhtin (1998) and Foucault (2002), as well as the challenges of translating scientific discourse for a lay audience (CALSAMIGLIA, 1997; CASSANY & MARTÍ, 1998; CATALDI, 2007, 2009). The study contributes to understanding how journalistic language participates in the public construction of scientific knowledge in contexts of health crises.